Preparedness for and management of organisational disruption in New Zealand : a descriptive exploration from the human resource management perspective : a thesis submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Human Resource Management at Massey University, Palmerston North, New Zealand - Ewing-Jarvie, Simon Antony (Massey University, 2001)
Business continuity planning and crisis management are the main terms used to describe the processes that organisations undertake when faced with disruption. Despite the economic and social importance of maintaining effective commercial activity most related research has been focussed on civil emergency and natural disaster or accident. There are a limited number of studies into organisational preparedness and no large studies in New Zealand. In particular, no studies have been found that focus on the human resource elements of organisational disruption. This research has sought to answer these questions through mail surveys, interviews and subsequent analysis. It has utilised the general style of an established questionnaire from researchers at the University of Southern California's Centre for Crisis Management to survey 1000 New Zealand organisations over two consecutive years. In addition, techniques developed in the field of knowledge engineering have been applied to the transcripts of the interviews conducted with senior executives and these have been developed into the domain layer of a knowledge model. The findings highlight that New Zealand organisations are poorly prepared for the complexities of the hazardscape, which is the term applied to a full spectrum approach to crisis management. In addition, the attitudes that prevail are similar to those found in the United States study of 1992. However, some unique findings have also been established. In particular, the influence of the Polynesian cultures has influenced some organisational cultures in a fatalistic manner. There are clear divisions of performance between the public and private sector and also within the public sector. New Zealand executives appear to be very compliance focussed. These and other findings now require the confirmation that will result from a continuation of a longitudinal study.
Keywords: Crisis management; Organisational disruption; Human resource management; New Zealand; Business continuity planning; Organisational preparedness; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management